Adsorption of methyl orange from aqueous solution onto calcined Lapindo volcanic mud - A. Jalil, Aishah; Triwahyono, Sugeng; Adam, S. Hazirah; Rahim, N. Diana; A. Aziz, M. Arif; H. Hairom, N. Hanis; M. Razali, N. Aini; A. Z. Abidin, Mahani; A. Mohamadiah, M. Khairul (Elsevier, 2010)
In this study, calcined Lapindo volcanic mud (LVM) was used as an adsorbent to remove an anionic dye, methyl orange (MO), from an aqueous solution by the batch adsorption technique. Various conditions were evaluated, including initial dye concentration, adsorbent dosage, contact time, solution pH, and temperature. The adsorption kinetics and equilibrium isotherms of the LVM were studied using pseudo-first-order and -second-order kinetic equations, as well as the Freundlich and Langmuir models. The experimental data obtained with LVM fits best to the Langmuir isotherm model and exhibited a maximum adsorption capacity (qmax) of 333.3 mg g-1; the data followed the second-order equation. The intraparticle diffusion studies revealed that the adsorption rates were not controlled only by the diffusion step. The thermodynamic parameters, such as the changes in enthalpy, entropy, and Gibbs free energy, showed that the adsorption is endothermic, random and spontaneous at high temperature. The results indicate that LVM adsorbs MO efficiently and could be utilized as a low-cost alternative adsorbent for the removal of anionic dyes in wastewater treatment.